Desarrollo de una plataforma para la evaluación de la calidad de servicio (QoS) que brinda el ISP MEGAred aplicando la metodología RAD. - Cabrera Toro, Daniel Fernando (2025)
Quality of Service (QoS) has become a key factor for Internet Service Providers (ISPs) due to the increasing demand for stable, high-performance connections. Users' perception of the quality of service provided largely depends on parameters such as connection speed, jitter, latency, and availability, which directly impact the user experience. However, ISPs face significant challenges in efficiently evaluating and optimizing these parameters, often leading to service deficiencies and decreased customer satisfaction. In this context, and given the lack of an adequate platform at ISP MEGAred, this research aimed to develop a technological platform to assess and improve the Quality of Service (QoS) provided by the company, applying the Rapid Application Development (RAD) methodology. The platform was designed using MATLAB, integrated with MySQL databases, and complementary tools such as Thing Speak, facilitating continuous análisis of key service parameters essential to ensuring end-user satisfaction. The platform's implementation allowed for precise performance evaluation and generated detailed reports that supported strategic and operational decision-making. Additionally, its integration with cloud tools ensured efficient data storage, thereby optimizing service management.